Association between prothrombin induced by vitamin K absence-II (PIVKA- II) and Barcelona Clinic Liver Cancer (BCLC) stage, tumor size, portal venous thrombosis in hepatocellular carcinoma patients - Darmadi, Darmadi; Ruslie, Riska Habriel (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hepatocellular carcinoma is one of the major cancer problems in the world because of the low early screening awareness in patients. Serum alpha-fetoprotein is not adequate as a single screening tool, especially for small HCCs, thus, prothrombin induced by vitamin K absence-II (PIVKA-II) can help in detecting small HCCs. Barcelona Clinic Liver Cancer (BCLC) stage remains to be the preferred HCC classification because it can predict the outcome and help in choosing available treatment options according to stages. This study aims to investigate the association between PIVKA-II levels with BCLC stage, tumor size, portal venous thrombosis in HCC patients. We enrolled patients with newly diagnosed HCC at the Adam Malik General Hospital, Medan, Indonesia from January to December 2018. Patients with HCC were classified according to BCLC stages, findings of portal venous thrombosis and tumor size from triphasic CT scan were noted, and serum PIVKA-II levels were measured. Sixty patients were included in this study. There were significant differences in serum PIVKA-II levels with different stages of BCLC (p < 0.001). Significantly higher serum PIVKA-II levels were detected in patients with portal venous thrombosis (p < 0.001) and larger size tumors (p < 0.003). Our study shows that serum PIVKA-II levels can help to diagnose, differentiate between stages of BCLC, and determine the prognosis in patients with HCC.